Selection Of Materials And Their Description In The Study Of The Grammatical Nature Of Phraseological Units - Qosimjonova Farangiz Farid qizi (International Journal Of Literature And Languages, 2025)
This article examines the selection and description of materials in studying the grammatical nature of phraseological units in Uzbek language. Emphasis is placed on the methodological importance of choosing resources that reflect linguistic structures and suit the research context. Principles such as generalizability, objectivity, and accuracy guide the selection of authentic, contemporary, and dialectal sources. Both traditional materials, like dictionaries, and modern software-based tools are analyzed to illustrate their role in revealing the syntactic, structural, and metaphorical features of idiomatic expressions. The study demonstrates that precise and methodologically sound material selection enhances the reliability and validity of research findings.